(3EOGQI GdCReGJ (B:s (3efgL GbJUGOj EOGQj dMd GdCReGJ Ydi eSJhi GdEbJUGO Gdbhej hGdhMOI GdEbJUGOjI (B/s - (3GdNVjQj, eMSf CMeOs ((3GdbGgQI(B: s (3ecJHI eOHhdj(B, s, 1990)
(3YGde GdCReGJ(B-(3GdCSS GdfXQjI GdYGeI dYde EOGQI GdCReGJ(B-(3GMJjGLGJ GdJYGed eY GdCReGJ(B-(3GdJYGed eY GdCReGJ(B-(3fMh efgL eJcGed ddJYGed eY GdCReGJ(B-(3aQjb GdegGe GdCRehjI(B-(3QSe SjfGQjhgGJ GdJYGed eY GdCReGJ(B-(3EOGQI eLJeY GdCReI(B-(3eGPG HYO GdCReIs
Keywords: (3EOGQIs; (3GdCReGJ GdEbJUGOjIs; (3GdEbJUGOs